Effects of oral creatine supplementation on high intensity, intermittent exercise performance in competitive squash players - Romer, L. M.; Barrington, J. P.; Jeukendrup, A. E. (International Journal of Sports Medicine, 2001)
The purpose of this study was to determine the effects of oral creatine supplementation on high intensity, intermittent exercise performance in competitive squash players. Nine squash players (mean +/- SEM &Vdot;O(2)max = 61.9 +/- 2.1ml small middle dot kg(-1) small middle dot min(-1); body mass = 73 +/- 3 kg) performed an on-court "ghosting" routine that involved 10 sets of 2 repetitions of simulated positional play, each set interspersed with 30 s passive recovery. A double blind, crossover design was utilised whereby experimental and control groups supplemented 4 times daily for 5 d with 0.075 g small middle dot kg(-1) body mass of creatine monohydrate and maltodextrine, respectively, and a 4 wk washout period separated the crossover of treatments. The experimental group improved mean set sprint time by 3.2 +/- 0.8 % over and above the changes noted for the control group (P = 0.004 and 95 % Cl = 1.4 to 5.1 %). Sets 2 to 10 were completed in a significantly shorter time following creatine supplementation compared to the placebo condition (P < 0.05). In conclusion, these data support existing evidence that creatine supplementation improves high intensity, intermittent exercise performance. In addition, the present study provides new evidence that oral creatine supplementation improves exercise performance in competitive squash players.